The Life-Cycle Effects of Pension Reforms: A Structural Approach - Daminato, Claudio; Padula, Mario (Journal of the European Economic Association, 2024)
To assess the life-cycle welfare effects of pension reforms, we provide a dynamic stochastic model of saving, portfolio choice, and retirement featuring a rich characterisation of the pension system. Relying on the exogenous variation from a sequence of Italian pension reforms, we identify and estimate the model, which is then used to draw implications of alternative pension policies. The validated model predicts substantial social security wealth effects on retirement, with the offset between public pension wealth and private savings softened when households can adjust their retirement decisions. We further find important distributional effects of pension reforms, with households’ welfare decreasing more the later in the working life they face the reform. Our findings have implications for the design of pension policies and the support they might generate.
Keywords: D15 - Intertemporal Household Choice; Life Cycle Models and Saving; E21 - Consumption; Wealth; H31-Household; H55-Social Security and Public Pensions; J26 - Retirement; Saving; Retirement Policies